Democratic Republic of Sao Tome and Principe : Third Review of the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criteria and Modification and Deletion of Performance Criteria Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Democratic Republic of Sao Tome and Principe. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This paper discusses key findings of the Third Review Under the Poverty Reduction and Growth Facility for Sao Tome and Principe. Structural reforms are progressing. Five of six structural benchmarks through September 2006 were met. The authorities strengthened public financial management (PFM) and laid the basis for tax reform and actions against money laundering. The 2007 agenda includes implementing a pilot PFM system and strengthening the environment for private sector activity. The draft 2007 budget shows significant consolidation efforts, given less favorable prospects for oil bonuses and the need to increase pro-poor spending.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet